Adagrasib in the Treatment of KRAS p.G12C Positive Advanced NSCLC: Design, Development and Place in Therapy - Warnecke B; Nagasaka M (Drug Design, Development and Therapy)
Brian Warnecke,1 Misako Nagasaka1,2 1Department of Medicine, University of California Irvine School of Medicine, Chao Family Comprehensive Cancer Center, Orange, CA, USA; 2Department of Medicine, St. Marianna University School of Medicine, Kawasaki, JapanCorrespondence: Misako Nagasaka, Department of Medicine, University of California Irvine School of Medicine, Chao Family Comprehensive Cancer Center, Orange, CA, 92868, USA, Email nagasakm@hs.uci.eduAbstract: One of the most common mutations seen in lung cancers are mutations in Kristen Rat Sarcoma Viral Oncogene Homolog (KRAS), observed in 25– 30% of patients with NSCLC. Mutations in KRAS result in oncogenesis via persistent activation of the MAPK/ERK pathways. Although once thought to be “undruggable”, KRAS p.G12C inhibitors such as sotorasib and adagrasib have been developed. This paper focuses on adagrasib, the second KRAS p.G12C inhibitor to obtain regulatory approval by the FDA and describes the details on its study design, development and current place in therapy.Keywords: Kristen Rat Sarcoma Viral Oncogene Homolog, sotorasib, AMG510, MRTX849, KRYSTAL, CodeBreaK, brain penetration